Electronic Business Revolution Opportunities and Challenges in the 21st Century - Cunningham, Peter; Fröschl, Friedrich (Springer Berlin Heidelberg, 1999)
Electronic Business will create changes similar to those brought about by the Industrial Revolution. It will change our business, society, and governance. It is happening now! Electronic Business is the integration of information technology (IT) and particularly the Internet into business processes. In the past 30 years IT has made processes more effective and efficient, but it has not fundamentally transformed them. Now, Electronic Business changes everything. The Internet is the catalyst: its eventual impact will be as great as or greater than that of the printing press. The aim of this book is to point out the challenges and opportunities facing Europe and its companies. It is based on the authors' joint experience of over 40 years with IT in business, industry, and government